Role of Governance and Public Trust on Government Debt-Economic Growth Nexus (A Global Empirical Analysis) - Andar Ristabet Hesda; Efi Yuliani (Future Science, 2021)
High government debts in several countries have the potential to trigger or exacerbate economic instability. These concerns are consistent with the results of this study, where countries that have a high debt ratio tend to have declining economic growth. To provide more understanding about this effect, this study tries to examine the effect of debt on economic growth by utilising the governance and public trust level as a contextual variable and mediator. Empirically, both variables have a prominent role in the debt and economic growth nexus. The debt threshold as a budgetary rule is necessary but might not be sufficient to validate the rationality of rising debt. The capability of government in providing public governance and the effect of additional debt on public trust is another crucial aspect that needs to be seriously scrutinised, or when the addition of debt becomes inevitable (such as in pandemic situation), the government should strengthen governance capability to ensure the productivity of debt and mitigate the decreased public trust. This finding implies that the debt policy should not only be based on budgetary rule but also the capacity of governance and the potential implication of the falling public trust.